MEMPREDIKSI INTENSI KEPATUHAN PAJAK GENERASI MUDA - Rossalina Christanti; Kezia Audrey Sazkhya Sinaga (Jurnal Riset Akuntansi dan Keuangan, 2023)
ABSTRACT Young generations are future taxpayers, future investors, future businessmen and businesswomen who will be the foundation of the country's economic system sustainability in the future. Awareness of paying taxes in the future should be a concern, especially in the scope of accounting education. This study intends to analyze the effect of normative belief on tax compliance intention. Tax literacy was also investigated as a moderating variable. Questionnaires were distributed to the young-adult age group, namely those who are still in college to those who are still in the position of entry-level taxpayers. Results show that normative belief has a significant effect on tax compliance intention, while tax literacy has also been shown to have a significant effect on tax compliance intention. Based on the results of data processing using the moderating variable test, it can be concluded that tax literacy is proven to strengthen the relationship between normative belief and tax compliance intention. The implications of this research are not only limited pragmatically to taxpayers and institutions as tax collectors. Implication of this research is primarily aimed at and will involve all stages of education, starting from primary to higher education institutions. Issues of tax awareness must be internalized, starting from a young age, so that knowledge related to tax benefits absorbed from the experience and reality of the Indonesian economy is also strengthened by tax knowledge provided in formal educational institutions. Keywords: Normative Belief, Tax Literacy, Tax Compliance Intention. ABSTRAK Generasi muda merupakan future taxpayers, future investors, future businessmen and businesswomen yang akan menjadi tumpuan keberlangsungan sistem perekonomian negara di masa depan. Kesadaran membayar pajak di masa depan harus menjadi perhatian terutama dalam lingkup pendidikan akuntansi. Penelitian ini bertujuan untuk menganalisis pengaruh normative belief terhadap intensi kepatuhan pajak. Literasi pajak juga diselidiki sebagai variabel moderasi. Kuesioner dibagikan kepada kelompok usia muda-dewasa, yaitu mereka yang masih kuliah hingga mereka yang masih berstatus wajib pajak entry level. Hasil penelitian menunjukkan bahwa normative belief berpengaruh signifikan terhadap intensi kepatuhan pajak, begitu juga pada literasi pajak terbukti berpengaruh signifikan terhadap intensi kepatuhan pajak. Berdasarkan hasil pengolahan data dengan menggunakan uji variabel moderasi, dapat disimpulkan bahwa literasi pajak terbukti memperkuat hubungan antara keyakinan normatif dengan intensi kepatuhan pajak. Implikasi penelitian ini tidak hanya terbatas secara pragmatis kepada wajib pajak dan instansi sebagai pemungut pajak. Implikasi penelitian ini terutama ditujukan dan akan melibatkan semua jenjang pendidikan, mulai dari pendidikan dasar hingga perguruan tinggi. Isu kesadaran pajak harus diinternalisasikan, dimulai sejak usia muda, agar pengetahuan terkait manfaat pajak yang diserap dari pengalaman dan realitas perekonomian Indonesia juga diperkuat dengan pengetahuan perpajakan yang diberikan di lembaga pendidikan formal. Kata kunci: Normative Belief, Literasi Pajak, Intensi Kepatuhan Pajak